Soil Dynamics in Carbon, Nitrogen, and Enzyme Activity Under Maize–Green Manure Cropping Sequences - Abreu-Junior, Cassio Hamilton; Melo, Wanderley José de [UNESP]; Oliveira, Roberto Alves de [UNESP]; Cardoso, Paulo Henrique Silveira; Dantas, Raíssa de Araujo; Sousa, Rodrigo Nogueira de; Silva, Dalila Lopes da; Nogueira, Thiago Assis Rodrigues [UNESP]; Jani, Arun Dilipkumar; Capra, Gian Franco; Melo, Gabriel Maurício Peruca de (MDPI, 2024)
The diversification of cropping sequences has a positive impact on soil organic carbon, while improving nutrient cycling and crop yields. The objective of this research was to assess amylase, cellulase, C and N dynamics, and maize yield on a low fertility oxisol in the Brazilian Cerrado. The experiment was conducted under field conditions during three maize crop succession cycles. The treatments consisted of cultivating maize during the summer, after sorghum and lablab cropped as green manure and fallow during the winter. Higher maize yields were achieved by sorghum–maize succession compared to monocropping, due to higher N fertilizer and biomass inputs to topsoil. Sorghum–maize succession also provided a higher proportion of stable C and N compared to other successions. Maize yields declined as tropical soil fertility intrinsically decreased along three crops succession cycles. Cellulase activity decreased over time, whereas amylase activity increased as the plant residues were already in advanced stages of decomposition. The sorghum–maize crop succession stood out compared to lablab and fallow as it provided the highest maize yields, while maintaining higher C and N levels, and amylase activity. This better performance was likely due to larger amounts of incorporated biomass and better mineral N fertilizer management.
Keywords: amylase; cellulase; Lablab purpureus; soil management; Sorghum bicolor